The reactor pressure effect on the reforming catalyst lifetime - Yakupova I. V. Inna Vagizovna; Kirillova M. D. Marina Dmitrievna; Chernyakova E. S. Ekaterina Sergeevna; Ivanchina E. D. Emilia Dmitrievna (2016, 2016)
Title screen